WHOLESALE STORE MANAGEMENT STRATEGIES TO SUPPORT THE ECONOMY OF ISLAMIC BOARDING SCHOOLS AND THE SURROUNDING COMMUNITY - Nuriawati; Mita Ayu Prafita; Uswatun Hasanah (IZZI: Jurnal Ekonomi Islam, 2026)
This study examines the strategic role of the Al-Mashduqiah Wholesale Store in supporting the economic independence of Islamic boarding schools while contributing to the surrounding community. Islamic boarding schools not only function as religious educational institutions, but also as drivers of the local economy that can empower the community and encourage the development of MSMEs. The research method used is qualitative with a descriptive approach, data obtained through interviews with shop managers, students, the community, and MSME actors. The results show that the Al-Mashduqiah Wholesale Store is able to support the needs of Islamic boarding schools, create jobs, provide basic necessities at affordable prices, and assist in the marketing of local products. These findings prove that Islamic boarding schools can play a role as a driving force for community-based economies, where aspects of education and economic empowerment go hand in hand